Kinetics of Fe–Ti Oxide Re-equilibration in Magmatic Systems: Implications for Thermo-oxybarometry. (25th January 2021) - Hou, Tong; Botcharnikov, Roman; Moulas, Evangelos; Just, Tobias; Berndt, Jasper; Koepke, Jürgen; Zhang, Zhaochong; Wang, Meng; Yang, Zongpeng; Holtz, François
Abstract: The combined Fe–Ti oxide geothermometry and oxygen barometry is an important tool in petrology and volcanology. However, its appropriate application to natural magmatic systems is still challenged by poorly constrained kinetics of the re-equilibration processes between magnetite, ilmenite, melt and other magmatic phases. In this study, we experimentally investigated how fast Fe–Ti oxides can re-equilibrate and how fast their compositions can adapt to changing temperature and/or redox conditions. A series of equilibrium crystallization experiments were conducted in internally heated gas pressure vessels using an evolved hydrous basaltic composition. These starting reference experiments were conducted at 200 MPa, at 900 and 1000°C and at two redox conditions, i.e. FMQ + 1 and FMQ + 3·3. The products of the starting experiments, all containing magnetite and/or ilmenite, were then placed at a different temperature (T) and/or oxygen fugacity ( f O2 ) for time dependent experimental series (1, 10 and 100 hours) in an attempt to check for the time needed for re-equilibration of the oxide composition. The experimental results demonstrate that both magnetite and ilmenite start to respond chemically to the changing conditions quite rapidly in less than 1 h. The largest compositional deviations from the equilibrium compositions were observed in the runs with 1 and 10 h duration. After 100 h, the Fe–Ti oxide compositions were approaching the expected equilibrium values in almost all kinetic series, but still with significant deviation. Moreover, our results clearly show that the Mg/Mn ratio in magnetite and ilmenite can follow the nominal 'equilibrium' trend, although the Fe–Ti distribution between oxides may not have reached equilibrium. This observation implies that the use of the Mg/Mn criterion to check for the equilibrium distribution of Fe–Ti between magnetite and ilmenite should be reconsidered or at least applied with caution. The quick, within-100-hours re-equilibration of the Fe–Ti oxides at magmatic conditions imposes limitations on the reliable application of oxide thermobarometry to natural systems. We suggest that in basaltic to andesitic volcanic rocks ascending and cooling relatively slowly (more than 5 days), the compositional T– f O2 record in oxides is representative of a late evolution stage rather than the pre-eruptive conditions in a magmatic reservoir at depth. This 'frozen' late-stage T– f O2 record is controlled by changing element diffusion rates with cooling and degassing. Only magmatic/volcanic systems, which underwent very rapid cooling, resulting from magma ascent within minutes or few hours (e.g. Plinian eruptions), can deliver Fe–Ti oxides reflecting the pre-eruptive magmatic T– f O2 signature.